2022
DOI: 10.3389/fped.2022.932366
|View full text |Cite
|
Sign up to set email alerts
|

Do not forget asthma comorbidities in pediatric severe asthma!

Abstract: Asthma is the most common chronic respiratory disease in childhood. The long-term goals in managing asthma aim to control symptoms and prevent exacerbations, as well as to reduce side effects of therapy and mortality disease-related. Most of patients have mild to moderate asthma and respond well to standard therapies. However, a minor proportion of children with asthma has severe disease that remains uncontrolled despite optimal adherence to prescribed therapy and treatment of contributory factors, including t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 82 publications
1
4
0
Order By: Relevance
“…This is consistent with all current asthma guidelines, including Global Initiative for Asthma (GINA) 6 and National Asthma Education and Prevention Program (Expert Panel Report 3, EPR‐3) 16 . It reflects good clinical practice (symptom and sign evaluation, which includes physical examination), the current philosophy of asthma management (based on disease control and prevention of exacerbations), and strong evidence demonstrating the role of comorbidities in adverse asthma outcomes 20,21 …”
Section: Recommendation Statementssupporting
confidence: 74%
See 1 more Smart Citation
“…This is consistent with all current asthma guidelines, including Global Initiative for Asthma (GINA) 6 and National Asthma Education and Prevention Program (Expert Panel Report 3, EPR‐3) 16 . It reflects good clinical practice (symptom and sign evaluation, which includes physical examination), the current philosophy of asthma management (based on disease control and prevention of exacerbations), and strong evidence demonstrating the role of comorbidities in adverse asthma outcomes 20,21 …”
Section: Recommendation Statementssupporting
confidence: 74%
“…16 It reflects good clinical practice (symptom and sign evaluation, which includes physical examination), the current philosophy of asthma management (based on disease control and prevention of exacerbations), and strong evidence demonstrating the role of comorbidities in adverse asthma outcomes. 20,21…”
Section: Statement 3 (Consensus Level 98%)mentioning
confidence: 99%
“… 111 The relationship between these two conditions is bidirectional, meaning that obesity can result from asthma, and asthma can also be brought on by obesity. 13 However, in children with asthma, obesity is linked to decreased asthma control and lung function, a lower quality of life, and a higher risk of asthma attacks. 112 Obesity is a known risk factor for increased hospitalizations in the pediatric intensive care unit.…”
Section: Evaluation and Management Of Damentioning
confidence: 99%
“… 134 In children with asthma, there is limited evidence as to whether such treatment is feasible. 13 The management of asthma, quality of life, and exacerbation risk may be optimized by breathing control exercises with the assistance of a skilled physiotherapist. 24 In a cohort study of 169 children with asthma and DB, it was found that, in addition to conventional medical therapy, individually tailored physical therapy interventions, namely Buteyko Breathing methods, improved asthma control and DB in kids receiving all levels of asthma medication.…”
Section: Evaluation and Management Of Damentioning
confidence: 99%
See 1 more Smart Citation